Risk factors for mental disorders in pregnant women in two cities from São Paulo, Brazil: A cohort study - Audêncio Victor; Maria Paula de Carvalho Leitão; Lívia Patricia Rodrigues Batista; Laisla de França da Silva Teles; Perla Pizzi Argentato; Liania A. Luzia; Rinaldo Artes; Patrícia Helen Rondó (PLoS ONE, 2025)
Introduction Mental disorders during pregnancy are a significant public health problem due to the substantial physiological and psychological changes that occur during this period. This study aims to investigate the risk factors for mental disorders in pregnant women by comparing data from two distinct cohorts in Jundiaí and Araraquara, Brazil. Methods This is a prospective cohort study that included pregnant women from two Brazilian cohorts in São Paulo state. The Jundiaí cohort (1997–2000) included 865 pregnant women, while the Araraquara cohort (2017–2024) included 755 pregnant women. Socioeconomic, demographic, obstetric history, and mental health data were collected and analyzed. Mental health was assessed using standardized questionnaires, including the General Health Questionnaire (GHQ), the State-Trait Anxiety Inventory (STAI), Trait Anxiety Inventory (TAI) and the Perceived Stress Scale (PSS). Statistical analysis included bivariate tests and univariate and multivariate random-effects models for panel data. Results Araraquara participants showed significantly higher GHQ scores at baseline (mean = 4.00) than Jundiaí (mean = 2.78; p < 0.001), with similar trends for SAI, TAI, and PSS. Scores decreased across visits in both cohorts (GHQ Visit 3: Coef. = –1.053, p < 0.001). Being single (GHQ: Coef. = 0.404, p = 0.019), separated/widowed (SAI: Coef. = 3.961, p = 0.005), lower education (TAI: Coef. = –1.910, p = 0.006), and higher household density (PSS: Coef. = 0.946, p = 0.012) were significant risk factors. Maternal morbidities such as urinary infections (TAI: Coef. = 0.862, p = 0.031), cervicitis/vaginitis (GHQ: Coef. = 0.290, p = 0.009), and tuberculosis (TAI: Coef. = 6.989, p = 0.033) were also strongly associated with worse mental health outcomes. Cohort differences remained significant even after adjustment (GHQ: Jundiaí vs Araraquara, Coef. = –1.357, p < 0.001). Conclusions This study showed that pregnant women in the more recent Araraquara cohort exhibited significantly higher levels of psychological distress symptoms, anxiety, and perceived stress than those in the earlier Jundiaí cohort. These mental health outcomes were strongly associated with lower per capita income, lower education levels, higher household density, and adverse pregnancy conditions such as urinary infection and gestational hypertension. These findings highlight the worsening social vulnerability of pregnant women over time and reinforce the urgency of incorporating systematic mental health screening into prenatal care policies in Brazil.